A Million Turnover Molecular Anode for Catalytic Water Oxidation. (7th November 2016) - Creus, Jordi; Matheu, Roc; Peñafiel, Itziar; Moonshiram, Dooshaye; Blondeau, Pascal; Benet‐Buchholz, Jordi; García‐Antón, Jordi; Sala, Xavier; Godard, Cyril; Llobet, Antoni
Abstract: Molecular ruthenium‐based water oxidation catalyst precursors of general formula [Ru(tda)(L i )2 ] (tda 2− is [2, 2′:6′, 2′′‐terpyridine]‐6, 6′′‐dicarboxylato; L 1 =4‐(pyren‐1‐yl)‐ N ‐(pyridin‐4‐ylmethyl)butanamide, 1 b ; L 2 =4‐(pyren‐1‐yl)pyridine), 1 c ), have been prepared and thoroughly characterized. Both complexes contain a pyrene group allowing ready and efficiently anchoring via π interactions on multi‐walled carbon nanotubes (MWCNT). These hybrid solid state materials are exceptionally stable molecular water‐oxidation anodes capable of carrying out more than a million turnover numbers (TNs) at pH 7 with an E app =1.45 V vs. NHE without any sign of degradation. XAS spectroscopy analysis before, during, and after catalysis together with electrochemical techniques allow their unprecedented oxidative ruggedness to be monitored and verified.